Family Business Operations and Sequel of Internationalisation in Nigeria - Akinbola, Amos Olufemi; Alaka, Nureni Sanusi; Kowo, Solomon Akpoviroro; Adeyemo, Adesola Alex (Economics and Business, 2020)
The concept of family business in Nigeria has become significantly attractive; its root is in sole proprietorship form of business. Family businesses have the unique strength to separate culture, language and personality. The research analyses the effect of interpersonal relationship on internationalisation and determines the extent to which succession planning affects internationalisation. Research presents that a positive relationship exists between internationalisation and interpersonal relationship. It has also been discovered that no positive relationship exists between succession planning and internationalisation. This study therefore concludes that family businesses which proceed to internationalisation enjoy growth in productivity, adequate brand awareness in the world, diversification of political and financial risks, as well as experience an increase in the share of the market, capital base, asset and open up opportunities in regional markets for workers. The study also recommends that employees in family businesses should communicate with each other effectively for a healthy relationship and managers should not make secret preparations for successors.